Civil Liability in the Use of Artificial Intelligence in Portugal: In particular in Medical Activity - Sousa Machado, Susana; Malta Fernandes , Maria (Law, State and Telecommunications Review, 2023)
[Purpose] In this article we intend to analyze the use of artificial intelligence (AI) in medicine and its consequences in terms of civil liability. This is because there are several damages that can be caused by electronic systems equipped with AI, especially if we consider their increasing evolution, autonomy and development. [Methodology/Approach/Design] The methodology of this scientific article is based on the research of doctrinal positions, both convergent and divergent, in order to present and discuss these doctrinal currents. Examples on the application of artificial intelligence to medicine are analyzed and, based on that basis, the necessary requirements for the verification of the obligation to indemnify are analyzed. [Findings] It is considered to what extent, and in order to make maximum use of the positive opportunities offered by these AI systems, the law has to shape up and introduce fair compensation procedures in case of harmful actions.